Empirical Studies Addressing the Opioid Epidemic: An Urgent Call for Research. (August 2018) - Stuart, Gregory L; Shorey, Ryan C; France, Christopher R; Macfie, Jenny; Bell, Kathryn; Fortner, Kimberly B; Towers, Craig V; Schkolnik, Paul; Ramsey, Susan
Opioid misuse has become one of the most pressing public health problems facing the country. In this article, we briefly review literature regarding the opioid epidemic in the United States and the negative consequences of opioid use disorder. We provide information regarding treatment and relapse using a variety of intervention approaches. We call for research on people with opioid use disorder that can contribute to a variety of areas: improving medication-assisted treatment, addressing chronic pain, examination of adjunctive behavioral interventions, overdose, high risk behaviors and infections, pregnancy, diverse populations, and other psychological factors. Collectively addressing these crucial areas of research will advance the field and help alleviate suffering and prevent death from opioid use disorder.